PLC Based Motor Coil Winding Measurement - Uttam, Deshmukh Vinayak; Bedi, Harpreet singh (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
Using PLC we can measure the coil windings for the motor. In which the PLC is used to give the command for the desired winding count. Coil winding is the difficult part of the motor when it gets affected and to repair that the count of the coil windings plays an important role. To Solve that solve that problem, PLC are used which will take the wing counts and then it will start the motor and when it will reach to that desired winding count it will stop. With that its used to find or calculate the RPM of motor also.